Hot-melt extrusion as an advantageous technology to obtain effervescent drug products - Lima, Ana Luiza (2020)
Here, we assessed the feasibility of hot-melt extrusion (HME) to obtain effervescent drug products for the first time. For this, a combined mixture design was employed using paracetamol as a model drug. Extrudates were obtained under reduced torque (up to 0.3 Nm) at 100 ◦C to preserve the stability of the effervescent salts. Formulations showed vigorous and rapid effervescent disintegration (<3 min), adequate flow characteristics, and complete solubilization of paracetamol instantly after the effervescent reaction. Formulations containing PVPVA in the concentration range of 15–20% m/m were demonstrated to be sensitive to accelerated aging conditions, undergoing marked microstructural changes, since the capture of water led to the agglomeration and loss of their functional characteristics. HPMC matrices, in contrast, proved to be resistant to storage conditions in high relative humidity, showing superior performance to controls, including the commercial product. Moreover, the combined mixture design allowed us to identify significant interactions between the polymeric materials and the disintegrating agents, showing the formulation regions in which the responses are kept within the required levels. In conclusion, this study demonstrates that HME can bring important benefits to the elaboration of effervescent drug products, simplifying the production process and obtaining formulations with improved characteristics, such as faster disintegration, higher drug solubilization, and better stability.